Morin decreases acrolein-induced cell injury in normal human hepatocyte cell line LO2. (December 2020) - Yin, Zhao; Guo, Hongyang; Jiang, Kaiyu; Ou, Juanying; Wang, Mingfu; Huang, Caihuan; Liu, Fu; Bai, Weibin; Zheng, Jie; Ou, Shiyi
Graphical abstract: Highlights: Morin decreases acrolein-induced cell damage in the LO2 cell line. It inhibits the expression of apoptotic markers and proinflammatory cytokines. It blocks the ERK/JNK/P38-MAPK signaling pathway. Abstract: Liver is the organ most frequently exposed to acrolein, a priority toxic pollutant. In the present study, whether morin can mitigate acrolein-induced cell damage in normal human hepatocyte cell line LO2 was investigated. Morin remarkably inhibited acrolein-induced apoptosis by inhibiting the expression of apoptotic markers, reducing the formation of proinflammatory cytokines, and blocking the ERK/JNK/P38-MAPK signaling pathway. The addition of equimolar morin decreased acrolein-induced cell apoptosis by 52.4%. The expression levels of apoptotic markers, BAX, Cyto-C, AIF, cleaved caspase-3/9, and PARP, decreased by 16%, 14%, 44%, 56%, 23%, and 45%, respectively. The proinflammatory cytokines, such as tumor necrosis factor α, inducible NO synthase, cyclooxygenase-2, interleukin 1β, and IFN-ϒ were reduced by 39%, 55%, 66%, 72%, and 64%, respectively. The phosphorylation level of ERK1/2, JNK, and P38 MAPK decreased by 10%, 47%, and 26%, respectively. The present findings may provide a way to mitigate acrolein-induced hepatic injury.